Synthesis and characterization of original fluorinated bis-cyclic carbonates and xanthates from a fluorinated epoxide - Alaaeddine, Ali; Ladmiral, Vincent; El Malti, Wassim; Haydar, Lolwa; Caillol, Sylvain; Améduri, Bruno (Comptes Rendus. Chimie)
The development of efficient methods for the cycloaddition of CX2 (carbon dioxide (X${=}$O) or carbon disulfide (X${=}$S)) with fluorinated epoxides to produce five-membered cyclic carbonates (CCs) or cyclic xanthates (XAs) is a very attractive topic. In this work, the cycloaddition of CX2 with hexafluoropropene oxide (HFPO) was performed in the presence of a lithium bromide (LiBr) catalyst and optimized in terms of temperature, solvent, pressure, and reaction time. Then, the optimized conditions were tried in the cycloaddition of CX2 with 2-(trifluoromethyl)oxirane (TFEO) for reproducibility, leading to the corresponding products in high yields. Finally, two original fluorinated five-membered bis-CCs and bis-XAs were synthesized in high yields (85 and 87%) by reacting CX2 with 1,4-bis($2^{′ }{,}3^{′ }$-epoxypropyl) perfluorobutane (BEPFB). All of the resulting compounds were characterized by FTIR, 1H, 19F, and 13C NMR spectroscopy.